Watching the war against Iraq through pan-Arab satellite TV - Mohamed El-Bendary (Asia Pacific Network, 2003)
It was the first Gulf War in 1991 which led to the satellite television explosion in the Arab world. Arabs then knew about Iraq’s invasion of Kuwait through CNN. Today, Arab satellite channels reach almost every Arab capital and many Middle Eastern and African nations — from Mauritania on the Atlantic coast to Iran in the east, from Syria in the north to Djibouti in the south. This battle for the airwaves and boom in satellite channels in the Arab world has become both a tool for integration and dispersion. It is raising a glimpse of hope that the flow of information will no longer be pouring from the West to the East, but from the East to the West. Questions, however, remain about the credibility of news coverage by Arabic networks like the maverick Qatar-based al-Jazeera and whether Arab journalists adhere to journalistic norms upheld in the West.